The effect of size, orientation and alloying on the deformation of AZ31 nanopillars. (March 2015) - Aitken, Zachary H.; Fan, Haidong; El-Awady, Jaafar A.; Greer, Julia R.
Abstract: We conducted uniaxial compression of single crystalline Mg alloy, AZ31 (Al 3 wt% and Zn 1 wt%) nanopillars with diameters between 300 and 5000 nm with two distinct crystallographic orientations: (1) along the [0001] c -axis and (2) at an acute angle away from the c -axis, nominally oriented for basal slip. We observe single slip deformation for sub-micron samples nominally oriented for basal slip with the deformation commencing via a single set of parallel shear offsets. Samples compressed along the c -axis display an increase in yield strength compared to basal samples as well as significant hardening with the deformation being mostly homogeneous. We find that the "smaller is stronger" size effect in single crystals dominates any improvement in strength that may have arisen from solid solution strengthening. We employ 3D-discrete dislocation dynamics (DDD) to simulate compression along the [0001] and [ 11 2 ¯ 2 ] directions to elucidate the mechanisms of slip and evolution of dislocation microstructure. These simulations show qualitatively similar stress-strain signatures to the experimentally obtained stress–strain data. Simulations of compression parallel to the [ 11 2 ¯ 2 ] direction reveal the activation and motion of only 〈 a 〉-type dislocations and virtually no dislocation junction formation. Computations of compression along [0001] show the activation and motion of both 〈 c + a 〉 and 〈 a 〉 dislocations along with a significant increase in the formation of junctions corresponding to the interaction of intersecting pyramidal planes. Both experiments and simulation show a size effect, with a differing exponent for basal and pyramidal slip. We postulate that this anisotropy in size effect is a result of the underlying anisotropic material properties only. We discuss these findings in the context of the effective resolved shear stress relative to the unit Burgers vector for each type of slip, which reveal that the mechanism that governs size effect in this Mg-alloy is equivalent in both orientations.